A study on the adoption of virtual reality in industrial design education - HAMURCU, AHMET (My University, 2023)
Virtual reality (VR) technology has been commercially and economically accessible to industrial designers for the past seven years, following the introduction of VR glasses and headsets, e.g., the HTC Vive and the Oculus Rift, in 2016. However, despite the growing popularity of VR implementations in education, it remains unclear to what extent industrial design (ID) students and instructors will adopt this technology. Hence, this paper discusses the limited adoption of VR technology in ID education based on the analysis of qualitative data obtained from ID students and instructors, specifically their perspectives on integrating VR into the education process. The data set comprises written and verbal expressions obtained through an online form and a group discussion session. The findings obtained from the analysis conducted through the content analysis approach suggest that both ID students and instructors harbor concerns regarding the incorporation of VR technology in ID education. These reservations primarily revolve around the potential adverse impacts of VR usage on students’ skill development in terms of manual dexterity and material knowledge, as well as the effectiveness of its implementation within the context of ID education.
Keywords: Endüstri Ürünleri Tasarımı; Industrial Design; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; MİMARİ; Arts & Humanities (AHCI); ARTS & HUMANITIES; ARCHITECTURE; Mimari; Fizik Bilimleri; Architecture; Physical Sciences; Industrial Design Education; Learning Environments; Learning Technologies; Virtual Reality